Technological Advancements: Effects on Local Economy Trends and Public Finance Dynamic - Andreadis, Eleftherios (My University, 2024)
This dissertation investigates the risks and opportunities arising from recent technological advancements, with a specific emphasis on the economic repercussions of cyberattacks targeting local entities in the United States and the adaption of artificial intelligence (AI) technologies within U.S. counties. The research offers insight into these implications by analyzing their impacts on both local economies and financial markets, with particular attention to the U.S. municipal bond market. Cyber attacks targeting local government entities pose significant challenges to municipal finances. This research investigates the economic repercussions of cyberattacks at the local government level. Employing a difference-in-differences approach to identify causal effects, the findings show significant increases in bond yields and reductions in bond issuance for municipalities situated in counties most exposed to cyberattacks targeting local entities and their pertinent news. Heterogeneous effects related to investor clientele suggest a capital supply channel. Municipalities respond to financing shortages by drawing their cash holdings and by reducing their more elastic investments. The awareness and prevalence of cybersecurity risk hinder local government entities’ access to capital by limiting their ability to provide public services and infrastructure. In parallel, the adoption of AI technologies at a local level presents opportunities for economic revitalization. This dissertation investigates the economic impact of AI technologies on municipalities using spatial variation in labor investments in artificial intelligence (AI). Employing an instrumental variable analysis, difference-in-differences regressions, and an entropy balancing approach, causal effects are identified while controlling for economic conditions and demographics. The findings show increases in labor investments in AI within a county lead to lower yields, which prompts municipalities to issue longer-term bonds. Qualitatively similar results that exploit the introduction of ChatGPT, further support causality. Differential effects of labor investments in Al within a region on economic activity and government revenues suggest an economic revitalization channel.
Keywords: cyberattacks